An Introduction to Neural Networks - David Bisant (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
Neural networks ares an important type of machine learning that have generated significant interest due to their success on difficult problems.. This tutorial will provide an introduction and a high-level overview of artificial neural networks. It will include the biological basis and the inspiration for these methods, and their colorful history.  An explanation of deep learning and deep belief networks, hardware acceleration, and case studies will be used to illustrate how the technology works and the direction in which it is developing.